2014
DOI: 10.1080/13540602.2014.953820
|View full text |Cite
|
Sign up to set email alerts
|

Moral stress in teaching practice

Abstract: The purpose of this article is to study whether moral stress is a phenomenon relevant to teaching practice and which may make a significant contribution to understanding why teachers repeatedly reported feeling burdened by work. Moral stress can be caused by acting in conflict with one's own conscience, e.g. when one knows the right thing to do but institutional constraints make it difficult to act in a way that is consistent with one's morals.The method used in this study is critical incident technique focusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 30 publications
(23 reference statements)
1
37
0
Order By: Relevance
“…Moral distress has previously been used to describe a particular form of stress or distress among professional nurses that could emerge when their working conditions prevent them from acting in accordance with their ethical guidelines (Jameton, 1984;Lützén & Kist, 2012;McCarthy & Deady, 2008). The concept has also been used recently to discuss teachers' experiences of ethical dilemmas as a result of their working conditions (Colnerud, 2013). Nevertheless, our analysis revealed that even children experience moral distress from time to time in the role of bystander in bullying situations in school.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moral distress has previously been used to describe a particular form of stress or distress among professional nurses that could emerge when their working conditions prevent them from acting in accordance with their ethical guidelines (Jameton, 1984;Lützén & Kist, 2012;McCarthy & Deady, 2008). The concept has also been used recently to discuss teachers' experiences of ethical dilemmas as a result of their working conditions (Colnerud, 2013). Nevertheless, our analysis revealed that even children experience moral distress from time to time in the role of bystander in bullying situations in school.…”
Section: Discussionmentioning
confidence: 99%
“…I don't know, but if they, I could resist quite a lot, but eventually, if they eventually wouldn't want to be friends with me, everyone says then they aren't real friends, but you don't want to lose them. (girl, grade 6) Peer pressure has a major impact on how bystanders respond (cf., Pozzoli & Gini, 2010, 2013Pozzoli et al, 2012;Rigby & Johnson, 2006), and those whom they define as their friends in the situation represent a major source of peer pressure.…”
Section: Friendshipmentioning
confidence: 99%
“…The working conditions in everyday practice make these needs hard to fulfil. This might be related to the moral stress that Colnerud (2015) reflects upon, implying a sort of conflict between teacher's professional judgements regarding proper ways to handle certain situations and constraining institutional conditions.…”
Section: The Empirical Data: Findings and Discussionmentioning
confidence: 99%
“…In his research, Biesta asserted that '…the culture of accountability makes it very difficult for the relations between parents/students and educators/institutions to develop into mutual, reciprocal, and democratic relationships, relationships that are based on a shared concern for the common educational good (or goods)-relationships, in other words, characterized by responsibility' (p. 249). We suggest that this might cause what Colnerud (2015) calls moral stress, which can occur when teachers are convinced of proper ways to handle various situations, while at the same time being constrained by institutional conditions. In these types of situations, teachers are shaped by reform contexts and discourses, as well as by the need to negotiate and provide resistance with the purpose of positioning themselves within both their local workplace and the existing national policy and reform climate (Buchanan, 2015).…”
Section: Gender and Care In Early Childhood Educationmentioning
confidence: 99%
“…Teaching has further been viewed to be imbued with moral dilemmas since teachers' acting in the class requires choices involving moral decisions (Tippins et al, 1993). Finally, the prescribed practices of the institutions or the institutional constraints make it difficult for teachers to act in a way that is consistent with their morals (Colnerud, 2015).…”
Section: Review Of Literaturementioning
confidence: 99%